Africa's land rush rural livelihoods & agrarian change - Hall, Ruth 1973-; Tsikata, Dzodzi 1962-; Scoones, Ian 1962- (James Currey, 2015)
Africa has been at the centre of a "land grab" in recent years, with investors lured by projections of rising food prices, growing demand for "green" energy, and cheap land and water rights. But suchland is often also used or claimed through custom by communities. What does this mean for Africa? In what ways are rural people's lives and livelihoods being transformed as a result? And who will control its land and agricultural futures? The case studies explore the processes through which land deals are being made; the implications for agrarian structure, rural livelihoods and food security; and the historical context of changing land uses, revealing that these land grabs may resonate with, even resurrect, forms of large-scale production associated with the colonial and early independence eras. The book depicts the striking diversity of deals and dealers: white Zimbabwean farmers in northern Nigeria, Dutch and American joint ventures in Ghana, an Indian agricultural company in Ethiopia's hinterland, European investors in Kenya's drylands and a Canadian biofuel company on its coast, South African sugar agribusiness in Tanzania's southern growth corridor, in Malawi's "Greenbelt" and in southern Mozambique, and white South African farmers venturing onto former state farms in the Congo. Ruth Hall is Associate Professor at the Institute for Poverty, Land and Agrarian Studies (PLAAS) at the University of the Western Cape, South Africa; Ian Scoones is a Professorial Fellow at the Institute of Development Studies (IDS) at the University of Sussex and Director of the ESRC STEPS Centre; Dzodzi Tsikata is Associate Professor at the Institute of Statistical, Social and Economic Research (ISSER) at the University of Ghana, Legon.
Title from publisher's bibliographic system (viewed on 21 May 2021)
List of maps, tables and figures -- Notes on contributors -- Preface -- Acknowledgements -- List of abbreviations -- Introduction: the contexts and consequences of Africa's land rush / Ruth Hall, Ian Scoones and Dzodzi Tsikata -- State, land and agricultural commercialisation in Kwara State, Nigeria / Joseph A. Ariyo and Michael Mortimore -- Recent transnational land deals and the local agrarian economy in Ghana / Joseph Awetori Yaro and Dzodzi Tsikata -- Large-scale land acquisitions in Ethiopia: implications for agricultural transformation and livelihood security / Maru Shete and Marcel Rutten -- Land deals and pastoralist livelihoods in Laikipia County, Kenya / John Letai -- Land deals in the Tana Delta, Kenya / Abdirizak Arale Nunow -- The state and foreign capital in agricultural commercialisation: the case of Tanzania's Kilombero Sugar Company / Emmanuel Sulle and Rebecca Smalley -- Trapped between the farm input subsidy programme and the green belt initiative: Malawi's contemporary agrarian political economy / Blessings Chinsinga and Michael Chasukwa -- Agrarian struggles in Mozambique: insights from sugarcane plantations / Gaynor Paradza and Emmanuel Sulle -- South African commercial farms in the Congo / Ruth Hall, Ward Anseeuw and Gaynor Paradza -- References -- Index
Keywords: Land tenure / Africa; Land use, Rural / Africa; Landnahme; Agrarstrukturpolitik; Auslandsinvestition; Neokolonialismus; Landwirtschaftliche Nutzfläche; Kleinbauer; Südliche Hemisphäre; Afrika; Aufsatzsammlung